Brand Love Co-Creation in a Digitalized Supply Chain Management: A Study on Framework Development and Research Implications - Ibrahim, Irwan; Amer, Afizan; Mat, Mustafa Kamal; Majid, Mohd Azlan Abdul; Jani, Siti Hajar Md. (International Journal of Supply Chain Management, 2019)
The study presents an integrative framework of brand love co-creation with theoretical underpinnings in joint with digital customer experiential creation of brand love. Main idea of this framework are brand love platforms entailing both relational activities and offerings, at the intersection of joint parties of experiential co-creators (whether in their role as customers) and co-creational enterprises as organizing the practice of brand love co-creation (whether in their role as innovating or marketing offerings or managing network relations). Using one illustrative examples of NEXT as an example of brand, the study discusses how brand love co-creation can be leverage through digital brand engagement platforms. Subsequently, using three independent variables, social-self, brand image and brand trust the study try to discuss the concept of co-creational enterprises as a nexus of co-creational digital platforms of engagements, and elaborate upon the organizational practice of brand love co-creation in a digitalized world. From the findings the study concludes with several implications for future brand research.